Pilot randomised trial of a brief intervention for comorbid substance misuse in psychiatric in‐patient settings. (21st November 2015) - Graham, H. L.; Copello, A.; Griffith, E.; Freemantle, N.; McCrone, P.; Clarke, L.; Walsh, K.; Stefanidou, C. A.; Rana, A.; Birchwood, M.
Abstract : Objective: This proof of principle study evaluated the effectiveness and feasibility of a brief motivational intervention, delivered in mental health in‐patient settings, to improve engagement in treatment for drug and alcohol misuse. Method: A randomised controlled trial using concealed randomisation, blind, independent assessment of outcome at 3 months. Participants were 59 new adult admissions, to six acute mental health hospital units in one UK mental health service, with schizophrenia related or bipolar disorder diagnoses, users of community mental health services and also misusing alcohol and/or drugs. Participants were randomised to Brief Integrated Motivational Intervention (BIMI) with Treatment As Usual (TAU), or TAU alone. The BIMI took place over a 2‐week period and encouraged participants to explore substance use and its impact on mental health. Results: Fifty‐nine in‐patients (BIMI n = 30; TAU n = 29) were randomised, the BIMI was associated with a 63% relative odds increase in the primary outcome engagement in treatment [OR 1.63 (95% CI 1.01–2.65; P = 0.047)], at 3 months. Qualitative interviews with staff and participants indicated that the BIMI was both feasible and acceptable. Conclusion: Mental health hospital admissions present an opportunity for brief motivational interventions focussed on substance misuse and can lead to improvements in engagement.